A magyar pedagógus társadalom motiváltsága a jövedelmek alapján = The motivation of educators in Hungary based on earnings - Horváth, Szilárd (Közép-Európai Közlemények, 2018)
Economic growth arguably depends on a well trained labour force. Accordingly, schooling citizens and maintaining a high quality of education are vitally important in every country. Hungary is regularly assessed in the triennial international PISA surveys - which evaluate students’ competence in mathematics, science, reading, problem solving and financial literacy. In 2015, Hungarian students were ranked 30th in reading comprehension among the participating 35 OECD countries. Numerous studies have demonstrated that the quality of education is greatly influenced by the pedagogical skills of teachers as well as their knowledge. The career structure for educators, which aims at incentivising people who work in education and preventing career change, was introduced on 1st September 2013. In Hungary, teachers’ earnings in the capital and in some northwestern counties are above the national average, whereas in some other counties salaries are significantly below average. This study investigates whether there is any recognisable correlation between the average level of teachers’ income and the incentives suggested by the career structure together with its purpose to prevent career change.